How data breaches lead to fraud. Issue 7 (July 2016) - Bush, Don
Abstract : The past few years have been particularly eventful and 2015 will be remembered for many momentous milestones. Those of us involved in security and fighting fraud online will remember it as a big year for major data breaches. A report carried out by PwC examining UK data breaches showed that not only had there been a rise in 2015 but that the scale and cost of these breaches had doubled. 1 The report concluded that data breaches, for large business, are "a near certainty". Many people will remember 2015 as a year of major data breaches. It wasn't just the sensitivity of the information but the variety of sources from which customer's data was compromised. These breaches happen because the data stolen is valuable. And in many cases the stolen data is considered valuable because it can be used to defraud businesses. But if organisations get smart and get prepared for fraud, this data won't be as valuable, explains Don Bush of Kount.